Nitrous oxide and carbon dioxide emissions from surface and subsurface drip irrigated tomato fields - Edwards, Kerri; Madramootoo, Chandra A; Whalen, Joann K.; Adamchuk, Viacheslav I; Mat Su, Ahmad Suhaizi; Benslim, Hicham (NRC Research Press, 2018)
Irrigation practices change the soil moisture in agricultural fields and influence emissions of greenhouse gases (GHG). A 2 yr field study was conducted to assess carbon dioxide (CO2) and nitrous oxide (N2O) emissions from surface and subsurface drip irrigated tomato (Solanum lycopersicum L.) fields on a loamy sand in southern Ontario. Surface and subsurface drip irrigation are common irrigation practices used by tomato growers in southern Ontario. The N2O fluxes were generally ≤50 μg N2O-N m⁻² h⁻¹, with mean cumulative emissions ranging between 352 ± 83 and 486 ± 138 mg N2O-N m⁻². No significant difference in N2O emissions between the two drip irrigation practices was found in either study year. Mean CO2 fluxes ranged from 22 to 160 mg CO2-C m² h⁻¹ with cumulative fluxes between 188 ± 42 and 306 ± 31 g CO2-C m⁻². Seasonal CO2 emissions from surface drip irrigation were significantly greater than subsurface drip irrigation in both years, likely attributed to sampling time temperature differences. We conclude that these irrigation methods did not have a direct effect on the GHG emissions from tomato fields in this study. Therefore, both irrigation methods are expected to have similar environmental impacts and are recommended to growers.